2020
DOI: 10.3390/ijerph17155284
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low-Frequency Magnetic Fields Exposure Measurement during Lessons in Elementary Schools

Abstract: Schools are an important place for children’s exposure to electromagnetic fields, which may cause adverse health effects. To better understand environmental extremely low-frequency magnetic fields (ELF-MFs) exposure among elementary school students, we measured numeric values of ELF-MFs in five classrooms at four schools during digital learning class hours. The measurement of ELF-MFs was taken with an EMDEX II field analyzer. Specifically, we examined the level of exposure to ELF-MFs for each student’s seating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Magnetic field levels up to 300 nT are considered within safe limits in most countries of the world. Several studies have shown that the field is regarded as potentially harmful from 400 nT to 1 µT, and dangerous from 1 µT and above [2,23]. Furthermore, the percentage magnetic field contribution (%) of each probe is available to the user to identify the plane direction (X, Y, or Z) of the incident magnetic field.…”
Section: Iot Application With Arduino Uno Wi-fi Rev2 Board For Real-t...mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic field levels up to 300 nT are considered within safe limits in most countries of the world. Several studies have shown that the field is regarded as potentially harmful from 400 nT to 1 µT, and dangerous from 1 µT and above [2,23]. Furthermore, the percentage magnetic field contribution (%) of each probe is available to the user to identify the plane direction (X, Y, or Z) of the incident magnetic field.…”
Section: Iot Application With Arduino Uno Wi-fi Rev2 Board For Real-t...mentioning
confidence: 99%
“…A considerable rise in blood triglycerides, a putative stress indicator in humans, the disorientation of chicks, and a reduced response time in monkeys are some unsettling effects of exposure to ELF fields [1]. Although some other research shows no link, epidemiological studies show a positive association between residential/domestic and occupational exposure to ELF fields and several forms of cancer, such as childhood leukaemia [2].…”
Section: Introductionmentioning
confidence: 99%
“…including separation distances and facility limits, have been implemented for places like kindergartens and elementary schools. These measures are put in place to shield children from ELF-MF emitted by power facilities, base stations, broadcasting stations, and other sources (Park et al, 2020).…”
mentioning
confidence: 99%